Groundwater and climate change: threats and opportunities - Stigter, Tibor Y.; Miller, Jodie; Chen, Jianyao; Re, Viviana (Hydrogeology journal, 2023)
The important role of groundwater in adaptation to climate change is explored, and the competing threats and opportunities that climate change pose to groundwater systems are evaluated. This has been achieved through a review of current thinking on the complex interactions between human activities, climate and the hydrological cycle affecting groundwater quantity and quality, across different regions and time scales.